Psychopathology, quality of life, and related factors in children with celiac disease - Eylem Sevinç; Fatih Hilmi Çetin; Banu Demet Coşkun (Brazilian Society of Pediatrics, 2017)
Objective: This study aimed to survey children with celiac disease (CD) for psychiatric disorders, determine the possible factors that predict psychopathology, and analyze health‐related quality of life and possible factors that could affect the quality of life. Methods: In this study, all children completed the Schedule for Affective Disorders and Schizophrenia for School Age Children-Present and Lifetime Version-Turkish Version (K‐SADS‐PL‐T), as well as the Pediatric Quality of Life Inventory (PedsQL) for the 8-12 age group, and a sentence completion test. A face‐to‐face interview was performed with the parents of the participants to inform them about the study. Results: This study included 52 children with celiac disease in the age range of 8-12 years, and 40 healthy children. The mean age of the study group was 10.36 ± 0.36 years, and 31 (59%) of them were females. The mean age of the control group was 10.35 ± 0.46 years and 24 (60%) of them were females. The mean subscale scores of the Pediatric Quality of Life Inventory were significantly lower in children with celiac disease when compared to the control group (p < 0.05). There was at least one psychiatric disorder in the 26 (50%) children with celiac disease. Conclusions: This study has shown once more that celiac disease is associated with some psychiatric signs/diagnoses, and that it decreased quality of life. Further studies are needed to determine the factors that could reduce the psychiatric signs. It is apparent that those studies would contribute new approaches to improve diagnosis, treatment, and quality of life.